The Use of Betamethasone in Women at Risk of Preterm Delivery Associated With the Incidence of Neonates Respiratory Distress Syndrome (NRDS), A Systematic Review - N. Alim, Fathi; D. Quartantri, Nadia; Ramadani, Rizka (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background : Neonatal Respiratory Disease Syndrome (NRDS) still become the most cause of neonatal’s mortality and morbidity especially in premature infants. Antenatal betamethasone has positive effect on preventing NRDS. Objectives : We sought to perform a systematic review of the use of bethametasone in women at risk of preterm delivery associated with the incidence of NRDS articles over the past fifty years. Methods: A systematic review was performed on PubMed and Scopus search term “Pediatrics” and “Pregnancy”. Results: Four articles identified between 2016 and 2019 specifically addressed for the use of betamethasone in women at risk of preterm delivery associated with the incidence of NRDS. A total 1800 patients were included in these four studies. The success rate range from 87,4% to 100%. Conclusion: Overall, the use of betamethasone in women at risk of preterm delivery decrease the incidence of respiratory distress syndrome in newborn significantly.